2000
DOI: 10.1038/80516
|View full text |Cite|
|
Sign up to set email alerts
|

Encephalitogenic potential of the myelin basic protein peptide (amino acids 83–99) in multiple sclerosis: Results of a phase II clinical trial with an altered peptide ligand

Abstract: Myelin-specific T lymphocytes are considered essential in the pathogenesis of multiple sclerosis. The myelin basic protein peptide (a.a. 83-99) represents one candidate antigen; therefore, it was chosen to design an altered peptide ligand, CGP77116, for specific immunotherapy of multiple sclerosis. A magnetic resonance imaging-controlled phase II clinical trial with this altered peptide ligand documented that it was poorly tolerated at the dose tested, and the trial had therefore to be halted. Improvement or w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
583
1
10

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 789 publications
(609 citation statements)
references
References 57 publications
13
583
1
10
Order By: Relevance
“…[1][2][3][4][5][6][7] Studies on human autoimmune diseases including SLE have reported amelioration of inflammatory responses and increases in CD4 þ CD25 þ Treg cells following treatment with self-antigen-derived peptides. [8][9][10][11][12][13][14][15][16] Similarly, self-antigen-derived peptides have also been used to induce immune tolerance and ameliorate disease in murine lupus models. 15,[17][18][19][20][21][22][23][24][25] Our group has developed a novel peptide pConsensus (pCons) that is based on MHC Class I and Class II T-cell determinants in the heavy chain region of murine anti-DNA IgG.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Studies on human autoimmune diseases including SLE have reported amelioration of inflammatory responses and increases in CD4 þ CD25 þ Treg cells following treatment with self-antigen-derived peptides. [8][9][10][11][12][13][14][15][16] Similarly, self-antigen-derived peptides have also been used to induce immune tolerance and ameliorate disease in murine lupus models. 15,[17][18][19][20][21][22][23][24][25] Our group has developed a novel peptide pConsensus (pCons) that is based on MHC Class I and Class II T-cell determinants in the heavy chain region of murine anti-DNA IgG.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports indicate that it contains epitopes for experimental autoimmune encephalomyelitis (Ohler et al 2004), a pathology which mimics multiple sclerosis. Recent clinical studies on the effects of MBP in multiple sclerosis patients have been published (Bielekova et al 2000). MBP belongs to the class of intrinsically unstructured proteins (IUP), and the unraveling of its structure is still a major unsolved problem in modern structural biology.…”
Section: Introductionmentioning
confidence: 99%
“…APLs have successfully been used as immunotherapeutic agents in experimental models of autoimmune diseases (29,30). An APL of myelin proteolipid protein, generated by substitution at a principal TCR contact residue of the encephalitogenic peptide, has been shown to prevent autoimmune encephalitis when mice were coimmunized with the APL and myelin proteolipid protein.…”
Section: Discussionmentioning
confidence: 99%
“…Although this does not ensure that a similar parallelism exists between our DR-transgenic mice and RA patients, it certainly provides a reasonable basis for development of reagents that might have therapeutic importance. Although the use of APL in the treatment of human disease is limited, 2 trials of APLs that were used to treat multiple sclerosis have produced some preliminary results (29,44). In fact, our preliminary studies, in which a low dose of rCII(N 263 , D 266 ) was administered to mice intravenously after the onset of severe arthritis, showed a reduction in the mean arthritis severity scores as compared with the controls administered PBS (Myers LK, et al: unpublished data).…”
Section: Discussionmentioning
confidence: 99%